A Case Study of Mechanical Strain in Supramolecular Complexes to Manipulate the Spin State of Iron(II) Centres. Issue 33 (5th November 2015) - Struch, Niklas; Brandenburg, Jan Gerit; Schnakenburg, Gregor; Wagner, Norbert; Beck, Johannes; Grimme, Stefan; Lützen, Arne
Abstract: Two novel supramolecular meso ‐helicates have been synthesized and characterized by single‐crystal X‐ray diffraction, variable‐temperature magnetic susceptibility measurements, NMR and UV/Vis spectroscopy, mass spectrometry and density functional theory (DFT) simulations. Both compounds show a considerably high stabilization of the high‐spin state of the metal centres compared with other compounds with similar types of ligands. Whereas the pyridyl complex [Fe2 L 2 3 ] [L 2 = N, N′ ‐bis(pyridin‐2‐ylmethylene)benzene‐1, 3‐diamine] exhibits the beginning of a spin transition at around 350 K, the imidazolyl complex [Fe2 L 1 3 ] [L 1 = N, N′ ‐bis(1 H ‐imidazol‐4‐ylmethylene)benzene‐1, 3‐diamine] still exhibits a high‐spin configuration at 20 K. We applied DFT to characterize the molecular as well as solid states of both compounds. Although the low‐spin state of both systems is stabilized by crystal packing, an additional stabilization of the high‐spin state is induced by intramolecular interactions. This effect can be ascribed to mechanical strain in the backbone of the ligands hailing from very short CH–π interactions and being similar in effect to sterically demanding methyl groups. Abstract : Two novel dinuclear supramolecular meso ‐helicates have been synthesized and studied by both experiment and theoretical (DFT) investigations to reveal a new intramolecular way to stabilize the high‐spin configuration of iron(II) complexes.